Single port laparoscopic and open surgical accesses of chronic peritoneal dialysis in children: A single center experience over 12 years - Ünal Biçakci; Gürkan Genç; Burak Tander; Mithat Günaydın; Dilek Demirel; Ozan Özkaya; Rıza Rızalar; Ender Arıtürk; Ferit Bernay (Journal of Minimal Access Surgery, 2016)
Introduction: The aim of this study was to evaluate patients with end stage renal failure (ESRD) who underwent chronic peritoneal dialysis (CPD). The clinical outcomes of laparoscopic and open placements of catheters were compared. Materials and Methods: We reviewed 49 (18 male and 31 female) children with CPD according to age, sex, cause of ESRD, catheter insertion method, kt/V rate, complications, presence of peritonitis, catheter survival rate between January 2002 and February 2014. Results: Thirty-three patients were with open placement and 16 patients were with laparoscopic placement. The rate of the peritonitis is significantly less in patients with laparoscopic access than open access (n = 4 v sn = 25) (P<0.01). Patients with peritonitis were younger than those who had no attack of peritonitis (10.95 ± 0.8 years vs 13.4 ± 0.85 years). According to the development of complications, significant difference has not been found between the open (n = 9) and laparoscopic (n = 3) approaches except the peritonitis. Catheter survival rate for the first year was 95%, and for five years was 87.5%. There was no difference between open and laparoscopic group according to catheter survival rate. The mean kt/V which indicates the effectiveness of peritoneal dialysis was mean 2.26 ± 0.08. No difference was found between laparoscopic and open methods according to kt/V. Conclusion: Laparoscopic placement of CPD results in lower peritonitis rate. Catheter survival rate was excellent in both groups. Single port laparoscopic access for CPD catheter insertion is an effective and safe method.